Effect of Early Weaning on the Intestinal Microbiota and Expression of Genes Related to Barrier Function in Lambs - Li, Chong; Wang, Weimin; Liu, Ting; Zhang, Qian; Wang, Guoxiu; Li, Fadi; Li, Fei; Yue, Xiangpeng; Li, Tingfu (Frontiers in Microbiology, 2018)
Weaning stress has been reported to impair intestinal health. The gut microbiota plays a vital role in the long-term health of the host. However, our understanding of weaning stress on gut microbiota and barrier function is very limited in livestock species, especially lambs. We investigated the effects of early weaning stress on intestinal bacterial communities and intestinal barrier function in lambs. A total of 24 neonatal male Hu lambs were randomly allocated into two groups, one weaned on day 28 and the other weaned on day 56. At 42 and 84 days, six lambs from each group were randomly selected and sacrificed. Ileal tissue and ileal digesta were collected to compare the differences in ileal microbiota and the mRNA levels of toll-like receptors (TLRs) and tight junction proteins between the early weaning group and the control group at day 42 when the early weaning group have been weaned for 14 days, and at day 84 when the 28 and 56 d weaning groups had been weaned for 56 and 28 days, respectively. 16S rRNA gene sequencing of ileal samples revealed that the ileal microbiota was very different between the two groups, even at 84 days of age. Early weaning significantly increased alpha diversity and altered the relative abundance of several bacterial taxa. The expression of genes related to intestinal barrier function was affected by early weaning. Early weaning significantly increased ileal mRNA levels of TLR1 on days 42 and 84; TLR2, TLR4 and TLR5 on day 84; claudin1 and claudin4 on day 42; and occludin on day 84. We demonstrate that early weaning not only altered the ileal microbiota on day 42 (compared with lambs that were not weaned), but also had lasting effects on the ileal microbiota at day 84; furthermore, early weaning impacts expression levels of genes related to intestinal barrier function.